Surface modification of TiO2 with ascorbic acid for heterogeneous photocatalysis:: Theory and experiment - Mert, E. Hilal; Yalcin, Yelda; Kilic, Murat; San, Nevim; Cinar, Zekiye (WALTER DE GRUYTER GMBH, 2008)
The photocatalytic activity of TiO2 particles was improved by surface modification with L(+)-ascorbic acid (AA), through the formation of a charge-transfer complex on the photocatalyst particles. In order to characterize and describe the effect of surface modification by AA on the electronic and structural properties of TiO2, a combination of experimental structural methods and DFT calculations were used. Surface modified photocatalysts with different AA contents were prepared by an incipient wet impregnation method and characterized by FTIR, XRD, SEM and UV-DRS. In the theoretical part of the study, a neutral, stoichiometric cluster Ti9O18 cut from the anatase bulk structure and a new model for the surface modified AA-Ti9O18 were developed. The DFT calculations were carried out by the hybrid B3LYP functional, which combines HF and Becke exchange terms with the Lee-Yang-Parr correlation functional by using double-zeta, LanL2DZ basis set. The formation process of the complex and its effect on the electronic structure of TiO2 were examined. The optimized geometries, the frontier-orbital energies, energy gaps, Mulliken charge distributions of the atoms on the surface were determined. The photocatalytic activity of the AA-modified TiO2 photocatalyst was also determined by investigating the kinetics of the photocatalytic degradation of hydroquitione, an environmentally important pollutant, in the presence of bare and surface modified TiO2.
Keywords: TiO2; DFT calculations; surface modification; ascorbic acid; heterogeneous photocatalysis; DOPED TIO2; DEGRADATION; WATER; PHOTOOXIDATION; NANOPARTICLES; PHENOL; Chemistry